A case study of developing gaze controlled interface for users with severe speech and motor impairment. - Jeevithashree, D.V.; Saluja, Kamalpreet Singh; Biswas, Pradipta (Technology & Disability, 2019)
BACKGROUND: People with severe speech and motor impairment (SSMI) often depend on electronic user interfaces for communication, learning and many other daily activities. However, these interfaces are often designed assuming the preference and ease of use of end users for different screen regions is the same for people with SSMI as their able bodied counterparts. This paper presents a user study to evaluate whether users can undertake pointing and selection tasks faster if screen elements are organized at their preferred positions. OBJECTIVE: To compare pointing and selection times in an eye gaze controlled interface between two conditions – screen elements randomly organized vs screen elements organized according to preference of users in terms of specific screen locations. METHODS: We designed a word construction game using familiar 4-letter words and users were instructed to select the correct letters to construct words. We compared total times required to construct each correct word. RESULTS: Users with SSMI can statistically significantly construct words faster [F(1,195) = 31.04, p < 0.01, η 2 = 0.14] when letters were organized at their preferred screen positions than random organization. CONCLUSIONS: Users with SSMI prefer middle and right side of screen more than the left side. Pointing and selection times in a gaze controlled interface can be significantly reduced by presenting screen elements at the preferred positions.